Biochemical Profiling and Physicochemical and Biological Valorization of Iraqi Honey: A Comprehensive Analysis - Omar Mohammed Hameed; Ohood Mzahim Shaker; Ahlem Ben Slima; Mohamed Makni (Molecules, 2024)
Our study aimed to analyze five monovarietal honeys from the Salah Eddine region in Iraq, focusing on physicochemical, antioxidant, and antimicrobial properties and polyphenolic compounds. Our objective was to evaluate the strengths and qualities of Iraqi honeys, ensuring compliance with the Codex Alimentarius standard for honey. The spectrophotometric analysis included assessments of reduced sugar (75.8–77.7%), fructose-to-glucose ratio (0.7–0.9%), sucrose (2.2–2.9%), HMF (17.23–18.87 mg/kg), and melanoidin content (0.25–0.44), which were all determined. The electrical conductivity (0.39–0.46 mS/cm) using a conductivity meter, pH (4.02–4.31), and mineral composition were determined in all samples using atomic absorption spectrometry. Antioxidant activities were spectrophotometrically determined, through DPPH free radical scavenging (7.87–95.62 mg/mL), as was the total antioxidant activity (14.26–22.15 mg AAE/g), with correlations established with biochemical constituents such as the total phenol content, highlighting the significant presence of Coumaric acid (0.38–2.34 µg/mL), Catechin (1.80–2.68 µg/mL), and Quercetin (0.30 µg/mL) using HPLC. The study also observed notable antimicrobial activities using Escherichia coli, Staphylococcus aureus, and Candida albicans on Mueller–Hinton agar as well as through diffusion technique. In conclusion, our findings, including the antioxidant and antimicrobial strengths, underscore the substantial potential of Iraqi honeys in mitigating damage and preventing the onset of various diseases, affirming their good quality and adherence to international honey standards.